Exploring entrepreneurial knowledge and usage of Islamic micro financing : a case study on Islamic guarantee Schemes of Credit Guarantee Corporation (CGC) / Ismail Ahmad ... [et al.] - Ahmad, Ismail; Ali, Husniyati; Pyeman, Jaafar; Osman, Muhamad Rahimi (Institute of Research, Development and Commercialization (IRDC), 2007)
In 2006, the Malaysian government implemented a sustainable and comprehensive microfinance institutional framework. Since then, many of the jinancial institutions have laun ched microjinance products. The Islamic finance as such can flourish in the Small Medium Enterprises (SMEs) and the microfinance sector since financing in Islam involves the real economy. The Islamic financing which is based on Shari'ah differs in its spirit and motivation as compared to the conventional one. This paper, attempts to explore the Islamic Guarantee Schemes services as provided by the Credit Guarant ee Corporation (CGC). What are the factors that could lead the SMEs to go for Islamic Guarantee Schemes and what are their perceptions and knowledge of Islamic financing? The data set utilized in this study has been obtained via a selfadministered questionnaire, based on samples of 125 CGC's clients. Results of the survey postulated that many of the entrepreneurs were not aware of the existence of Islamic Guarantee Schemes, and their knowledge pertaining to the Shari 'ah principles of Islamic microfinancing is rather shallow. The results have important implications to the policy makers in strengthening the use of Islamic microfinancing among SMEs. The CGC also must work with a concerted effort with participating financial institutions to market these schemes to other entrepreneurs, who may be looking f or alternative modes of financing, which are Shari'ah compliant.